Thick - Greene, Anthony M.; Brown, Cheryl M.; Dae, Tia; Piquion, Pascale; Benson-El, Ronald; Skyrocket Productions; Leomark Studios (Firm) ([Waco, Texas] : Skyrocket Productions, LLC, 2014)
Theresa James is a burgeoning apartment complex magnate who runs illegal businesses in her neighborhoods for added financial gain. Feeling the aftermath of the 2010 Recession, Theresa tries to regain a foot hold in her underworld, professional and private life as her employees start to undermine her by looking for a way out of her fledgling criminal empire. --
Originally released as a motion picture in 2014
Tia Dae, Pascale Piquion, Ronald Benson-El, Chaseedaw Giles, Mick McGuire, Caleb Jackson, E. Martin Ealy, Jonathon Lee Taylor.
Cinematographer, Omar Juarez ; editors, Omar Juarez, Manuel Santos ; music
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 2, 2018)
Keywords: African American criminals -- Drama; Crime films; Feature films; Internet videos; Streaming video